The Influence of Raw Material Quality and Production Process on Product Quality in Melinjo Chips MSMEs in Pucangan Village, Ambal District, Kebumen Regency - Ulfa Tikasari; Wijayanti; Dedi Runanto (IECON: International Economics and Business Conference, 2025)
The purpose of this research is to investigate how the quality of raw materials and the production process affect the final product quality of melinjo chips produced by MSMEs in Pucangan Village, Ambal District, Kebumen Regency. MSMEs are very important for the Indonesian economy, especially in terms of reducing unemployment and creating job opportunities. However, with the increasing business competition, entrepreneurs must become more competitive, which includes improving the quality of their products. This study uses a survey approach and is quantitative in nature. The research sample, consisting of 90 respondents, was selected using purposive sampling, and the population consists of melinjo chip craftsmen in Pucangan Village. Using SPSS software, data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that product quality is positively and significantly influenced by production procedures and raw material quality, both partially and jointly. These results indicate that improving the quality of raw materials and streamlining production procedures may be important tactics for enhancing the competitiveness of MSME products.